Aplicación móvil para el aprendizaje de la lengua Taushiro en instituciones educativas de nivel primaria de la ciudad de Iquitos 2023 - Muñoz Andrade, Hubert (2023)
The objective of this research is to improve the learning of the Taushiro language in primary level Educational Institutions in the city of Iquitos through the use of a mobile application, for which the evaluation of the recognition of basic elements of communication, mathematics and indigenous culture in the Taushiro language was carried out. It is intended that this app called "Ivá" (baby in Taushiro) serve as a didactic support in schools to maintain and preserve the Taushiro language, which is in danger of extinction and currently has only one speaker over 65 years of age. Being, the question to solve: How the use of a mobile application, significantly improves the learning of the Taushiro language in Educational Institutions of primary level of the city of Iquitos? Then, to evaluate, a quasi-experimental design with post test and control group was taken into account, with a non-probabilistic sample for convenience, made up of sixty (60) students of the 2nd grade of primary school of the I.E. N° 61014 "Horacio Zevallos Gámez", from the city of Iquitos. Where, the results obtained show that with the use of a mobile application, the learning of the Taushiro language can be improved, statistically verifying that the students managed to significantly increase their level of recognition of the aforementioned basic elements. Finally, it was concluded that more than 80% of the students managed to obtain a "good" level in the recognition of the basic elements in the Taushiro language, that is to say that with the use of this tool said students obtained grades equal to or greater than sixteen (16), being a very valuable data for the teaching-learning process, and that through this we would be contributing to maintaining and preserving the Taushiro language.